PENGARUH INSENTIF MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN MASA KERJA SEBAGAI VARIABEL MODERASI DI KANTOR REDAKSI HARIAN PAGI LAMONGAN (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of the study was to determine the effect of incentives and motivation on employee performance with length of service as a moderation variable at the editorial head of the morning daily Suara Umum Lamongan. This study used a quantitative descriptive research method approach involving 50 respondents with techniques used in purposive sampling sampling. The instrument used is a questionnaire. The results showed the effect of incentives on employee performance with an incentive variable calculation value of 2.406, greater than the table of 2.01290 and a sig value of 0.020 smaller than 0.05. And there is an influence of motivation on employee performance with a calculated value of work motivation variables of 2.432 greater than ttable 2.01290 and a sig value of 0.019 smaller than 0.05. However, the calculated value of the working period moderation variable of 0.050 is smaller than the table of 2.01290 and the sig value of 0.745 is greater than 0.05 and it is concluded that the working period variable does not moderate incentives for employee performance, and the calculated value of the working period variable of 0.081 is smaller than the table of 2.01290 and the sig value of 0.450 is greater than 0.05 and it is concluded that the working period variable does not moderate motivation for employee performance.